Reciclagem de polímeros para contato com alimento e o uso de sistemas de leito fluidizado na etapa de descontaminação - Bonatti, Sophia Helena Felisbino (Universidade Federal de São Carlos, 2024)
Polymer recycling represents an important approach to the maintenance of environmental, energetic and economic health of the planet, with the key parts of sustainable solutions development being the valorization of recycled resins and the feasibility of their use in rigorous applications. Nowadays, many recycling processes are well-established, including the ones that aim for demanding applications such as food contact materials, with special focus on PET-PCR resins (i.e., post-consumer recycled PET). However, post-consume resins from other natures are also widely available, such as PP, PE and PS, and they must be directed to recycling to stimulate circularity and sustainability, as well as they should not be detached from food contact materials application. Hence, the challenges associated with the decontamination and the mechanical recycling of these resins must be approached more deeply and more suitable process must be developed, aiming to obtain PCR (post-consumer recycled) resins whose properties are equivalent to those of virgin resins and that are sufficiently decontaminated to not offer risks during their use. Fluidized bed systems, which are already well-established in the industry, offer interesting advantages and can assist in the chemical decontamination step, mainly for favoring diffusion processes.
Polymer recycling for food contact application and the use of fluidized bed systems at the decontamination step
Keywords: Polímeros; Reciclagem; Pós-consumo; Contato com alimento; Leito fluidizado; Polymer; Recycling; Post-consumer; Food contact; Fluidized bed; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::POLIMEROS